A Very Rare Case of Polycythemia Vera Patient Who Developed Other Four Cancers - Romeo-Gabriel Mihaila (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2017)
We find more and more often patients with two or more synchronous or metachronous cancers, who raise various issues on the risk factors and pathways. A polycythemia vera male patient, diagnosed at 44 years, evolved towards secondary myeloid metaplasia which was then transformed into secondary acute myeloid leukemia. He also presented breast adenocarcinoma and a basal cell carcinoma of the nasal pyramid and of the internal angle of the left orbital region during those 13 years of evolution. Pathogenetic mechanisms are discussed, as well as the followed treatments and their effectiveness. The appearance of the four new malignancies infl uenced his quality of life and have reduced his survival.